3D Human Activity Classification with 3D Zernike Moment Based Convolutional, LSTM-Deep Neural Networks - Ozbay, Erdal; Cinar, Ahmet; Ozbay, Feyza Altunbey (Int Information & Engineering Technology Assoc, 2021)
In this paper, we propose a method for classification 3D human activities using the complementarity of CNNs, LSTMs, and DNNs by combining them into one unified architecture called CLDNN. Our approach is based on the prediction of 3D Zernike Moments of some relevant joints of the human body through Kinect using the Kinect Activity Recognition Dataset. KARD includes 18 activities and each activity consists of real-world point clouds that have been carried out 3 times by 10 different subjects. We introduce the potential for the 3D Zernike Moment feature extraction approach via a 3D point cloud for human activity classification, and the ability to be trained and generalized independently from datasets using the Deep Learning methods. The experimental results obtained on datasets with the proposed system has correctly classified 96.1% of the activities. CLDNN has been shown to provide a 5% relative improvement over LSTM, the strongest of the three individual models.
Keywords: classification; CNN; DNN; LSTM; 3D human activity; 3D Zernike moment